Profiling Selebriti Fraud: Analisis Profil Koruptor di Indonesia - Septarina Prita DS; Siti Maria Wardayat; Endah Liyati; Ananda Firly MS (ITB AAS INDONESIA, 2020)
This study aims to analyze the profile (profiling) of corruptors in Indonesia. This research was conducted because it saw the problem of corruption in Indonesia as endless. Many government officials from the central government to local governments have been caught by the Komisi Pemberantasan Korupsi (KPK) in carrying out various types of corruption. Losses experienced by the country reached trillions of rupiah. Therefore, efforts to fight, eradicate and prevent corruption in Indonesia can be done through profiling analysis. This research is a qualitative research with descriptive method. The object of this research is the entire biodata of corruption convicts on the official website of the KPK (https://acch.kpk.go.id/id/jejak-kasus) during 2005 to 2016. The results of the study show that corruptors in Indonesia are 89% Male and state losses reached Rp1,159,101,252,520,-; 43.6% have S1 education and cause state losses of up to Rp180,936,238,257,-; 49% occupy the position of top/executive and cause state losses amounting to Rp 859,333,150,609,-; 72% are in government agencies; and organizations that are often victims of corruption 81.2% are government agencies.